Short Film of Adolescent Reproductive Health Based on Friendly of Local Wisdom for Junior High School in Bondowoso - Tantut Susanto; Kholid Rosyidi Muhammad Nur; Soekma Yeni Astuti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Background: The lack of information and low knowledge for adolescent reproductive health (ARH) have an impact on junior high school (JHS) students during puberty to develop unhealthy reproductive behaviors, such as dating and consumption of pornography through online media. Meanwhile, there are lack of facilities and infrastructure to accommodate the interests and talents of students that are friendly with local wisdom. Therefore, there is needed a partneships program between schools and university to improve student creativity for coaching ARH through empowerment of school environment. Furhermore, the aim of community egagement is to make a short film “healthy ARH” that is friendly to local wisdom to improve life skills of ARH.Method:The crativity of short movie program “healthy ARH” for local wisdom-friendly was conducted for 6 months at JHS 2 and JHS 3 Tamanan, Bondowoso. Among 36 students, 34 parents, and 6 teachers were participated in this program. Student creativity for making a short film was facilitated for promoting and education of ARH. This activities is an independent program from, by, and for students and teachers which are friendly with local wisdom. The series of activities consisted of community school consultations, training for made a short film, education and training for ARH, and monitoring and evaluation of program. Program measurements for students were performed through quantitatively measured for analyzed the differences of knowledge, attitudes, and behavior of ARH, as well as knowledge of HIV at the beginning of month 1, month 3, and month 6 using Chi square test. Whereas the qualitative evaluation was perforemed through focus group discussions (FGD) regarding the perceptions of students and teachers used a short film as ARH promotion media at the end of the program.Hasil:Among 36 students who took part in this program, there were significant differences for ARH of students before and after participating in the “healthy ARH” through short film based on local wisdom-friendly, both in terms of knowledge(X2= 33.6; p<0.001), attitudes(X2= 16.2; p=0.001), behavior(X2= 24.3; p<0.001), andknowledge ofHIV (X2= 11.9;p=0.008). Based on the FGD, the teachers were feel confident for conducting peer counselors using short film education media. These film was easier to educate the student regarding the values and norms of school environment. Meanwhile, students feel comfortable learning ARH from a short film and their interests and talent are facilitated by short film creativity.Kesimpulan:Ashort film “healthy ARH” based local wisdom-friendly program is able to improve the knowledge, attitudes and behavior of ARH, as well as the students' HIV knowledge. This program could be used as a medium for ARH education in schools by integrating with the school health program to improve life skills of ARH.